WORLD OUTLOOK POTENTIAL OF CULTUROLOGY - Victor I. Polischuk (Высшее образование в России)
The article presents the reflections on the importance, value, and the content of today’s Russian youth outlook. The culture studies as a complex of various disciplines and self-consciousness of modern culture can serve as a basis and means for formation of students’ necessary outlook. Knowledge of any type is knowledge about culture. Culturological approach as an alternative to technocratic thinking focuses on research activities and contributes to formation of holistic outlook.